Efficacy of Purtscher's Retinopathy Treatments: A Systematic Review. (3rd June 2017) - Xia, Duosheng; Chen, Xiaomei; Zhou, Qi; Xiao, Shujun; Yu, Yang; Wang, Yadong; Du, Gang; Huang, Haixiang; Zhang, Wenfang; Chen, Yaolong
ABSTRACT: Objective : The aim of this review is to evaluate the efficacy of available Purtscher's Retinopathy treatments. Materials and Methods : In order to collect single-case reports, electronic searches were conducted in several databases including PubMed, Embase, Web of Science, China National Knowledge Infrastructure, SinoMed, VIP, and WanFang in the Electronic Theses and Dissertations Center. In VIP and Wanfang, we also traced the references of included articles. Risk of bias was evaluated using a tool adapted from the Cochrane Risk of Bias Tool. Statistical analysis was done in SPSS19.0. Evidence was evaluated and graded with GRADE system. Results : In total, 76 studies were included involving 88 cases and 139 eyes. Serious bias existed in 90% of the included studies. Current treatments for Purtscher's retinopathy included glucocorticoid therapy (63.29%), traditional Chinese medicine therapy (10.13%), glucocorticoid integrative medicine therapy (7.60%), and integrative medicine therapy (6.33%). Patients' eyesight with (56.83%) or without (43.17%) treatment both improved in the follow-up within 1–3 months, 4–6 months, and more than 6 months; however, conditions without treatment became better compared to the treatment groups in after 4–6 months and more than 6 months. All results were "very low" in the GRADE system. None of the studies reported adverse reactions in any patient. Conclusions : Both treatment and no treatment improve vision in Purtscher's retinopathy patients, but the difference between no treatment and glucocorticoid therapy had no statistical significance. The evidence quality for this conclusion was "very low" and had large bias. Further research is required to understand the safety of Purtscher's retinopathy treatment.